ECOLOGICAL WISDOM OF KAMPUNG NAGA AS LEARNING RESOURCE FOR ELEMENTARY SOCIAL STUDIES - Fauziah, Syifa; Agustin, Mubiar; Alditia, Lalu Muhammad; Sugiri, Syifa Salsabila (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2025)
Humans are creatures that rely on nature as a place to meet their needs. However, often the exploration of nature turns into exploitation that destroys nature until it loses its usefulness. Some indigenous peoples are people who still hold fast to the noble values of their ancestors. One of these indigenous peoples is the indigenous people of Kampung Naga in Tasikmalaya. The main study conducted by the researcher is to identify the values of local ecological wisdom of the local culture of the Kampung Naga community which can be a reference in social studies learning in elementary school grade V. This study uses a qualitative method with an ethnographic approach that studies the cultural values in Kampung Naga, through interview techniques with two informants, namely tourguides and experts in the fields of Geography, observation,  and documentation studies. The results of the study show that the traditional village community of Kampung Naga has local ecological wisdom values, both in terms of regional spatial planning, disaster mitigation, environmental conservation, daily consumption patterns, spring protection, prohibited forest protection, agricultural activities, and fisheries conservation. Unique ecological value can also be found by the separation of the area into the upper (sacred), middle (neutral), and lower (gross) areas. The value of disaster mitigation and environmentally friendly consumption patterns also exists in taboos or pamali which are still a guideline for the people of Kampung Naga.